More than 'canaries in the gender coal mine': A transfeminist approach to research on detransition. Issue 4 (July 2020) - Hildebrand-Chupp, Rowan
Detransition is tied to three related but distinct concepts – the act of detransitioning, the 'detransitioner' identity, and the negative transition experience – which I refer to collectively using the umbrella term 'detrans'. Detrans research is inevitably political and value-laden, but different methodologies and research questions lend themselves to divergent goals. Drawing on work in the feminist philosophy of science and transfeminist scholarship, I draw a conceptual distinction between research aligned with the goals of 'preventing detrans' vs. 'supporting detrans'. Existing research has constructed detransition as a negative clinical outcome to be prevented because it has been focused on the causes of detrans and the detrans rate. Research associated with the goal of supporting detrans is defined by its focus on the experience and process of detrans itself. Research on preventing detrans constructs detrans as a divisive issue of zero-sum clinical risk, and it is not oriented toward helping people who detransition or who have a negative transition experience. Research on supporting detrans, in contrast, constructs detrans as an issue of inclusion and can be used to improve the medical and mental health care that detrans people receive. I argue that there is an urgent need for qualitative sociological research involving detrans people. I conclude with some broad guidelines for researchers studying detrans.